General Military Training Standardization and Reduction Options - Yardley, Roland J. (RAND Corporation, 2012)
Every uniformed service member must complete general military training requirements prescribed by his or her service and the U.S. Department of Defense (DoD). DoD wants to reduce cyclic mandatory training requirements, reducing the training burden on the services and making the most of available training time. This report examines mandatory training requirements and options to standardize requirements and reduce the training burden.